Research on Soil Cutting with a Flat Cutter Using a Simulation Model - Asset Altynbayev; Alexandr Ganyukov (Communications)
The research aims to develop an algorithm for modelling the process of cutting an infinite volume of soil with a flat cutter in the Abaqus software package. The hypothesis of the existence of energy and volume of resistance to cutting is proposed. The analysis of shock wave distribution in the soil volume is performed. Boundary conditions for the soil volume model are determined, as well as for a flat cutter with linear motion. Stress gradients in the soil during its deformation are determined. Confirmation of the hypothesis about the existence of energy and volume of resistance to cutting was obtained. A logarithmic regression equation was derived based on the obtained volume values.